Studies in Polish Morphology and Syntax - Hentschel, Gerd; Laskowski, Roman (Specimina philologiae Slavicae, 1993)
This volume presents a sampling of papers devoted to different phenomena of Polish (and theoretical) morphology and syntax. The focus of attention of the Authors of the present volume is concentrated mostly on questions of syntactic and morphological analysis of Modern Standard Polish with exception of W. Mańczak's and (in part) G. Hentschel's articles, which take the diachronic perspective.